Non-femoral focused transaxillary access in TAVI: GARY data analysis and future trends - Meertens, Max M.; Adam, Matti; Beckmann, Andreas; Ensminger, Stephan; Frerker, Christian; Seiffert, Moritz; Sinning, Jan-Malte; Bekeredjian, Raffi; Walther, Thomas; Beyersdorf, Friedhelm; Möllmann, Helge; Balaban, Ümniye; et al. (Clinical research in cardiology, 2025)
Background In patients not suitable for transfemoral transcatheter aortic valve implantation (TAVI), several access strategies can be chosen. Aim To evaluate the use and patient outcomes of transaxillary (TAx), transapical (TA), and transaortic (TAo) as alternative access for TAVI in Germany; to further evaluate surgical cutdown vs. percutaneous TAx access. Methods All patients entered the German Aortic Valve Registry (GARY) between 2011 and 2019 who underwent non-transfemoral TAVI were included in this analysis. Patients with TA, TAo, or TAx TAVI were compared using a weighted propensity score model. Furthermore, a subgroup analysis was performed for TAx regarding the percutaneous or surgical cutdown approach. Results Overall, 9686 patients received a non-transfemoral access. A total of 8918 patients (92.1%) underwent TA, 398 (4.1%) TAo, and 370 (3.8%) TAx approaches. Within the TAx subgroup, 141 patients (38.1%) received subclavian cutdown, while 200 (54.1%) underwent a percutaneous approach. The TA patients had a significantly lower 30-day survival than TAx patients (TA 90.92% vs. TAx 95.59%, p = 0.006; TAo 92.22% vs. TAx 95.59%, p = 0.102). Comparing percutaneous and cutdown TAx approaches, no significant differences were seen. However, more vascular complications occurred (TA 1.8%, TAo 2.4%, TAx 12.2%; p < .001), and the hospital length of stay was shorter (TA 12.9 days, TAo 14.1 days, TAx 12 days; p < .001) after TAx access. Conclusion It may be reasonable to consider TAx access first in patients not suitable for TF-TAVI, because the 30-day survival was higher compared with TA access and the 1-year survival was higher compared with TAo access. It remains important for the heart teams to offer alternative access modalities for patients not amenable to the standard TF-TAVI approaches. Graphical Abstract